PENDUGAAN CADANGAN KARBON DI ATAS PERMUKAAN TANAH PADA AREAL LAHAN GAMBUT EKSKEBAKARAN DI DESA TUMBANG NUSA, KABUPATEN PULANG PISAU: Yudha dan Afentina - Administrator Journal (Agrienvi: Jurnal Ilmu Pertanian, 2019)
ABSTRACTThis study was conducted to determine the stored carbon stock, types of vegetation in the study sites andthe influence of forest fire. This research used standard method used by group of researchers whose joininginternational network: Alternative to Slash and Brun (ABS) with observation subplot 5 m x 40 m = 200 m2, vegetationbiomass measurements of 5 – 30 cm and > 30 cm (if any), biomass measurements of lower plants (understory, d < 5cm), measurements of necromass that present at the soil surface. This research was conducted at an ex-firedpeatland area of Tumbang Nusa Village, Cental Kalimantan. The results showed that vegetation biomass based onthe distribution of diameter class of 5 – 30 cm has a large biomass of 2,607.16 Mg ha-1 because in the 5 – 30 cmdiameter class the vegetation contained in it was a type of tree that has a large biomass content, whereas thenecromass was low i.e. 44.93 Mg ha-1, because few trees and woody necromass. The carbon stock in the study areawas 1,242.88 Mg ha-1; this figure was small.Keywords: Carbon Stock, biomass, necromass